MAKNA SIMBOLIS DALAM GERAKAN TARI ADAT TRADISIONAL SUKU KABOLA KECAMATAN KABOLA KABUPATEN ALOR: PERSPEKTIF ANTROPOLOGI BUDAYA - Adventia Korang; Adesti A. Kamba; Acia Blegur La; Miseri C. Lau; Adol Bria; Halena Muna Bekata; Petrus Mau Tellu Dony (CV. ADIBA ASIHA AMIRA, 2025)
This research examines the meaning of symbols in traditional dance movements in Kabola District, Alor Regency using a cultural anthropology perspective. The purpose of the research is to reveal and analyse the deep meaning of various symbols contained in the traditional dance movements of the Kabola community. The research method used is qualitative with an ethnographic approach, involving field observations and interviews. The results showed that Kabola traditional dance movements have symbolic meanings that are closely related to the belief system, social values, and worldview of the local community. Each dance movement represents various aspects of life such as human relationships with nature, respect for ancestors, fertility, and social harmony. The waving upward movement of the hands symbolises communication with the ancestors, while the rhythmic stomping of the feet depicts the strength and robustness of tradition. This research contributes to a deeper understanding of Indonesia's rich culture, particularly in the context of the Kabola community, as well as highlighting the importance of preserving traditional values in the modern era.